2019
DOI: 10.1080/17457289.2019.1604528
|View full text |Cite
|
Sign up to set email alerts
|

Emotions, cognitions and moderation: understanding losers’ consent in the 2016 Brexit referendum

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…More recent works have started taking the within winner group differentiation into account noticing that the effect of winning is more pronounced among those with an attachment to their party (Singh, 2014). Similarly, others have found that the impact of winning on satisfaction is moderated by the relative performance of the party that one supports (e.g., Curini et al, 2015) or by political sophistication (Nadeau et al, 2019). None of these studies, however, has taken into account a crucial differentiation among all citizens, namely the initial level of attachment to and perceived legitimacy of the democratic regime.…”
Section: Catalyst Of Love or Alienation Effect?mentioning
confidence: 99%
See 1 more Smart Citation
“…More recent works have started taking the within winner group differentiation into account noticing that the effect of winning is more pronounced among those with an attachment to their party (Singh, 2014). Similarly, others have found that the impact of winning on satisfaction is moderated by the relative performance of the party that one supports (e.g., Curini et al, 2015) or by political sophistication (Nadeau et al, 2019). None of these studies, however, has taken into account a crucial differentiation among all citizens, namely the initial level of attachment to and perceived legitimacy of the democratic regime.…”
Section: Catalyst Of Love or Alienation Effect?mentioning
confidence: 99%
“…Such studies show that winning in a district is rather unimportant, but the results are mixed: for example, Blais and Gélineau (2007) find an independent effect of winning at the district level whereas Anderson and LoTempio (2002) and Henderson (2008) do not. Lastly, there exists some literature on the winner-loser gap in EU referendums in Germany, Finland, and the Netherlands (Brummel, 2020) and in the Brexit referendum (Nadeau et al., 2019; Schaffner, 2020). Albeit not directly focused on satisfaction with democracy, these studies suggest a moderate but positive effect of winning a referendum on support for direct democracy and the acceptance of the referendum result.…”
Section: Accepting Electoral Defeat Celebrating Victory?mentioning
confidence: 99%
“…The fact that the Brexit vote was very close makes the question on loser consent even more pressing (Howell and Justwan 2013). Here, research by Nadeau at al. (2019) shows a robust level of loser consent among Remain voters, especially for the politically more moderate ones.…”
Section: The Case Of Brexitmentioning
confidence: 99%
“…Bellamy, 2019), while support for a ‘no deal’ Brexit gradually became the dominant position within the Leave camp (Kettell and Kerr, forthcoming; Staiger et al ., 2019). 4 In the immediate aftermath of the referendum positions had, surprisingly, been more moderate: Many Leavers spoke about the benefits of the ‘Norway model’, while Remain supporters acted, on the whole, as ‘graceful losers’ (Nadeau et al ., forthcoming) and Remain-mobilisation was initially low (Davidson, 2017). Third, political parties began to shift their own positions over the course of 2018–19: The Conservatives spoke more favourably of ‘no deal’ under Johnson, Labour flirted with the idea of a second referendum and eventually adopted it, the Brexit Party set out a harder stance than had UKIP – which had not supported a no deal Brexit – and the Liberal Democrats moved from promising a second referendum to promising a revocation of Article 50.…”
Section: The European Election and British Politicsmentioning
confidence: 99%